2005
DOI: 10.1124/dmd.105.003988
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mouse Organic Anion-Transporting Polypeptides (Oatps) in Liver by Prototypical Microsomal Enzyme Inducers That Activate Distinct Transcription Factor Pathways

Abstract: ABSTRACT:Drug-metabolizing enzymes and transporters are key factors that affect disposition of xenobiotics. Phase I enzyme induction by classes of microsomal enzyme inducers occurs via activation of transcription factors such as aryl hydrocarbon receptor (AhR), constitutive androstane receptor (CAR), pregnane X receptor (PXR), peroxisome proliferator-activated receptor ␣ (PPAR␣), and nuclear factor erythroid 2-related factor 2 (Nrf2). However, regulation of organic anion-transporting polypeptide (Oatp) uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 31 publications
7
99
1
Order By: Relevance
“…For example, TCDD is found in burnt trash; phenobarbital is used for treating seizures; and ethoxyquin, a quinoline-based antioxidant, is used as a food preservative. These chemicals at the dosages used in this study were found to up-regulate cytochrome P450 enzymes in rats and mice (Hartley and Klaassen, 2000;Cheng et al, 2005). However, the present study indicates that only a few chemicals induce Mdr transporters.…”
Section: Regulation Of Mouse Mdr Transporterscontrasting
confidence: 47%
“…For example, TCDD is found in burnt trash; phenobarbital is used for treating seizures; and ethoxyquin, a quinoline-based antioxidant, is used as a food preservative. These chemicals at the dosages used in this study were found to up-regulate cytochrome P450 enzymes in rats and mice (Hartley and Klaassen, 2000;Cheng et al, 2005). However, the present study indicates that only a few chemicals induce Mdr transporters.…”
Section: Regulation Of Mouse Mdr Transporterscontrasting
confidence: 47%
“…However, this mechanism leads to smaller differences in rosuvastatin kinetics compared with competitive inhibition. We acknowledge that the regulation of OATP1 expression is complex, and other transcription factors such the constitutive androstane receptor, pregnane X receptor, peroxisome proliferator-activated receptor, farnesoid X receptor, and small heterodimer partner may play a role in regulating OATP1B1 expression as these factors have been found in the promoter and enhancer region of Oatp2 in rats (Cheng et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…After several incubation and washing steps, streptavidin-conjugated R-phycoerythrin fluorescence was analyzed by a Bio-Plex 200 system array reader interfaced with Bio-Plex data manager software 5.0 (Bio-Rad Laboratories, Hercules, CA). The majority of the genes quantified in the current study have been previously characterized by our laboratory (Cheng et al, 2005;Klaassen, 2006, 2008a,b;Buckley and Klaassen, 2007;Cheng and Klaassen, 2009). Details of the plex sets used in the current study can be found at www.panomics.com with the following numbers: 21073, 21150, 21152, 21153, 21174, and 21175.…”
Section: Methodsmentioning
confidence: 99%